Experimental study of using aerofoils in a refrigerated display cabinet. (May 2022) - Yuan, P.; Zeng, Q.H.; Wu, Y.X.; Lu, Y.L.; Hu, C.L.; Sun, H. C; Tao, W. Q
Highlights: The food refrigerated display cabinet with aerofoil structures is studied experimentally. The aerofoil structures have a great influence on the air curtain flow of the refrigerated display cabinet. The total power consumption of food refrigerated display cabinet with aerofoil structures can be reduced by 21.7%. Abstract: In this paper, the performance of a refrigerated open-type multi-deck display cabinet with and without aerofoil structures was investigated experimentally under the condition of test chamber for climate level 3 (25°C and 60% RH). The test results showed that by installing aerofoil structures, the maximum temperature difference of food in the test cabinet was decreased by 0.6°C, the heat entrainment factor was reduced by 38.7 % - 50 %, and the total power consumption was reduced by 21.7 %.